Haemozoin formation, effects of chloroquine on iron distribution in Plasmodium falciparum and the correlation of thermordynamic and structural factors with 4-aminoquinoline activity - Mabotha, Tebogo E (Department of Chemistry, 2014)
Includes bibliographical references (leaves 178-191).